Efficacy of Saffron ( L.) and Its Constituents on Breast Cancer, a Systematic Review of Preclinical Studies and Potential Therapeutic Mechanisms - Fatemeh Sadat Hasheminasab MD, PhD; Maryam Azimi MD, PhD (Integrative Cancer Therapies)
Background: Breast cancer is the most common cancer and the main cause of death because of malignant tumors in women, worldwide. The impact of Crocus sativus on several cancers has been discussed. Recent studies provide evidence regarding the anticancer properties of C. sativus and its bioactive constituents against breast cancer. This study aims to systematically review the efficacy of this botanical drug and its constituents on breast cancer, and their mechanism of action for the first time. Due to the lack of human studies in this field, the present research focused on preclinical studies. Methods: In this systematic review, scientific databases, including PubMed, Web of Sciences, Google Scholar, Scopus, and Scientific Information Database were explored profoundly. Preclinical studies published until the end of 2024 that had investigated the therapeutic properties of C. sativus , or its bioactive constituents including crocin, crocetin, safranal, or picrocrocin against breast cancer were selected. Results: Forty-four studies examining the effect of C. sativus or its bioactive constituents against breast cancer were obtained. Preclinical in vitro and in vivo studies have demonstrated the potential and targeted anticancer properties of the metabolites found in saffron ( C. sativus ). These metabolites, such as crocin, crocetin, and safranal, exhibit their anticancer effects through various mechanisms, including induction of apoptosis, modulation of the cell cycle, and other pathways. Conclusions: C. sativus and its constituents exerts their anticancer activity with different mechanisms. A considerable number of the included studies highlight induction of apoptosis and modulation of the cell cycle. The findings of our study suggest that certain compounds, particularly crocin and crocetin, have significant anticancer properties. In particular, crocin provided the highest level of evidence of efficacy in preclinical research, indicating its potential for further investigation.